(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the direct impact of the globalization process on language policy, particularly the dominant position of the English language in the international arena. The factors leading to the widespread dissemination of English globally are explained based on historical, political, and technological reasons. Furthermore, the article highlights the effects of this process on local languages, such as the Uzbek language, covering phenomena like language mixing (code-switching), lexical distortions, and the devaluation of the native language. A linguistic analysis is conducted on the positive and negative aspects of these situations. The article also provides recommendations regarding the necessary balance in state policy, cultural policy, and measures to be taken in the field of education in order to preserve our native languages.